Afrikaanse Reseptiewe Woordeskattoets (ARW): Toepaslikheid Vir In Groep Nie-Standaardafrikaanssprekende Kinders - Mariekie Buitendag; Isabel Uys; Brenda Louw (South African Journal of Communication Disorders, 1998)
The need for culturally approp1iate language tests served as motivation for this study. The aim of the study was to evaluate the suitability and adaptability of It he Afrikaanse Reseptiewe Woordeskattoets (ARW) (Buitendag, 1994) for a group of seven and ten year old non-standard Afrikaans speaking children from the coloured community in Gauteng, North West, Mpumalanga and Northern Province. In orde1r to achieve this goal the ARW (Buitendag, 1994), and a questionnaire regarding socio-economic deprivation, were administered to a proportionally stratified randomized sample of 960 children. Test bias was evaluated by comparing the psychometric characteristics of the test for the research group to those of the normative group. Various test adaptation procedures were considered, namely adaptations to the rank order of item difficulty, test starting points and test procedures. The results indicated the same degree of confidence in the test results of the two groups. It demonstrated that the original rank order of item difficulty does not need to be changed and that corresponding increase in ARW scores is evident with an increase in age in both groups. The findings imply that the test measures the same ability in the two groups. Although comparison of the psychometric characteristics of the test for the research group to those for the normative group failed to identify test bias, intra-group comparison indicated that the test may be linguistically biased against the socio-economically deprived sub-group. Significant differences in individual ARW scores occurred when a shift in the child's basal or ceiling item occurred as a result of the biased items. The test's cultural validity for the group may be increased by lowering the test starting points, in order to prevent reversed testing. Culturally appropriate responses should be accepted as correct, in order to award equal credit to standard and non-standard language responses and to take intra-group differences into consideration. This research is an important contribution towards the expansion of the speech-language therapist's skills and resources, vitally needed to provide culturally relevant services in South Africa to all individuals with communication disorders.